1998
DOI: 10.1121/1.421734
|View full text |Cite
|
Sign up to set email alerts
|

Using fish sounds to identify spawning activity of weakfish (Cynoscion regalis) and red drum (Sciaenops ocellatus) in nature

Abstract: In the coastal systems of the southeastern United States, populations of weakfish (Cynoscion regalis) and red drum (Sciaenops ocellatus) are in decline, and knowledge of their spawning areas is important for the for- mulation of fisheries management plans. Weakfish and red drum, both members of Family Sciaenidae, use their swim bladders to produce species-specific sounds associated with spawning activity. Large spawning aggregations of these fish can produce sound levels as high as 145 dB (re:1 μPa), and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both the reef/off-reef paired recordings and the sound propagation surveys demonstrate the importance of the higher frequency band in distinguishing the oyster reef soundscape, and this is reinforced by the 2011 Clam Shoal propagation survey, which showed that the lower frequency band was not distinct to the reef habitat. Since this frequency band encompasses sounds produced by aggregations of the sciaenid fishes common in Pamlico Sound environments (Sprague et al 1998, Luczkovich et al 2008, the re-emergence of the low frequency peak in the recordings at 1500 and 2000 m was likely due to proximity to other sources of fish sounds such as the numerous seagrass beds and shoals in the Clam Shoal area. Because the 2010 survey did not extend to these distances, we cannot assess whether the lower frequency trend detected at Clam Shoal in 2011 was due to a transient event (e.g.…”
Section: Habitat-related Acoustic Characteristicsmentioning
confidence: 99%
“…Both the reef/off-reef paired recordings and the sound propagation surveys demonstrate the importance of the higher frequency band in distinguishing the oyster reef soundscape, and this is reinforced by the 2011 Clam Shoal propagation survey, which showed that the lower frequency band was not distinct to the reef habitat. Since this frequency band encompasses sounds produced by aggregations of the sciaenid fishes common in Pamlico Sound environments (Sprague et al 1998, Luczkovich et al 2008, the re-emergence of the low frequency peak in the recordings at 1500 and 2000 m was likely due to proximity to other sources of fish sounds such as the numerous seagrass beds and shoals in the Clam Shoal area. Because the 2010 survey did not extend to these distances, we cannot assess whether the lower frequency trend detected at Clam Shoal in 2011 was due to a transient event (e.g.…”
Section: Habitat-related Acoustic Characteristicsmentioning
confidence: 99%